Individual Variation in Heat Substitution - Maloney, Caroline (Université d'Ottawa / University of Ottawa, 2022)
Endotherms living in cold environments must pay the energetic cost of maintaining a high core body temperature. This cost can be potentially alleviated by an important yet often overlooked mechanism: “activity-thermoregulatory heat substitution” (i.e., the use of the heat generated by active skeletal muscles to replace heat that would have been generated by thermogenesis). While substitution has been documented numerous times, the extent of individual variation in substitution has never been quantified. I used a respirometry cage system to repeatedly measure substitution through the concomitant monitoring of metabolic rate (MR) and locomotor activity in 46 female white-footed mice (Peromyscus leucopus) in neutral and cold ambient temperatures. I took a total of 117 measures of substitution by quantifying the difference in the slope of the relationship between MR and locomotor activity speed at two different ambient temperatures. Consistency repeatability (±se) of substitution was 0.313±0.131 – hence, about a third of the variation in substitution occurs at the among-individual level. Including key morphological traits such as trunk surface area, tail mass, heart mass, and body length accounted for the majority of the among-individual variation, suggesting that I have successfully identified traits underlying individual differences in substitution. Overall, my results show that substitution is repeatable and hence might potentially be subject to selection. Future studies should test if substitution conveys fitness advantages directly (by providing energetically cheaper activity which in turn can be utilized for reproduction), or indirectly (i.e., driven by individual differences in morphology). Future studies should also test if there is a trade-off between substitution and dry heat transfer (a thermoregulatory mechanism essential for preventing hyperthermia).
Keywords: evolutionary physiology; environmental physiology; energetics; thermal biology; functional ecology